Prognostic analysis of endovascular mechanical thrombectomy in stroke patients with acute internal carotid artery obstruction based on circle of Willis variation - Qiu, Tianlun; Luo, Huagang; Bao, Wuqiao (Frontiers in Neurology, 2025)
ObjectiveEndovascular mechanical thrombectomy (EVMT) is widely employed in patients with acute intracranial carotid artery occlusion (AIICAO). This study aimed to predict the outcomes of EVMT following AIICAO by utilizing anatomic classification of the circle of Willis and its relative position to the thrombus.MethodsIn this study, we retrospectively analyzed a cohort of 108 patients with AIICAO who underwent endovascular mechanical thrombectomy (EVMT) at Shaoxing People’s Hospital. Based on variations in the circle of Willis, as well as the size and location of the thrombus occluding the middle cerebral artery (MCA), anterior cerebral artery (ACA), and posterior cerebral artery (PCA), we classified AIICAO into four grades using digital subtraction angiography (DSA). EVMT was initiated upon admission, and baseline data including demographic characteristics, vascular risk factors, angiographic features, initial National Institutes of Health Stroke Scale (NIHSS) scores, Alberta Stroke Program Early CT Score (ASPECT), and etiology classification were compared across these four grades. The prognosis and mortality rates at 90 days post-stroke were evaluated for the different grades and within each grade, patients were further categorized into two subtypes based on vascular compensation and occluded vessels.ResultsSignificant differences were observed among the four grades of Willis compensation concerning etiologic classification (p = 0.008), postoperative modified treatment in cerebral ischemia (mTICI, p = 0.017), postoperative symptomatic intracranial hemorrhage (sICH, p = 0.007), NIHSS score at admission (p = 0.001), and favorable outcomes at 90 days (modified Rankin Score 0–2) (p = 0.003). The mortality rate at 90 days exhibited a significant difference across the four grades of Willis compensation (p = 0.05). However, prognosis did not reveal any significant differences among the various subtypes within the same grade (p > 0.05).ConclusionThe assessment of the degree of Willis compensation can be improved by evaluating the integrity of the circle of Willis, as well as the size and location of the clot in cases of isolated internal carotid artery occlusion (iICAo). This approach provides valuable prognostic indicators and important insights for the pre-selection of patients prior to endovascular mechanical thrombectomy (EVMT).